2023
DOI: 10.3390/ijms242216205
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of CircRNA Expression Profiles in Multiple Tissues of Pigs

Qingpeng Shen,
Wentao Gong,
Xiangchun Pan
et al.

Abstract: Circular RNAs (circRNAs) are a class of non-coding RNAs with diverse functions, and previous studies have reported that circRNAs are involved in the growth and development of pigs. However, studies about porcine circRNAs over the past few years have focused on a limited number of tissues. Based on 215 publicly available RNA sequencing (RNA-seq) samples, we conducted a comprehensive analysis of circRNAs in nine pig tissues, namely, the gallbladder, heart, liver, longissimus dorsi, lung, ovary, pituitary, skelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…circRNAs are endogenous noncoding RNAs that are found in various species and tissues and play important roles in animal tissues [ 43 ]. Previous research has shown that circIPO11 can activate the hedgehog signaling pathway to drive the self-renewal of liver cancer-initiating cells and promote the proliferation of hepatocellular carcinoma (HCC) cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs are endogenous noncoding RNAs that are found in various species and tissues and play important roles in animal tissues [ 43 ]. Previous research has shown that circIPO11 can activate the hedgehog signaling pathway to drive the self-renewal of liver cancer-initiating cells and promote the proliferation of hepatocellular carcinoma (HCC) cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%